PENGEMBANGAN KOMPETENSI GURU DALAM PENULISAN ARTIKEL ILMIAH DAN PENGGUNAAN MENDELEY - Nabilla, Ulya; Nurviana, Nurviana; Lydia, Ellida Novita; Amelia, Amelia; Muliani, Fitra; Sari, Riezky Purnama; Fairus, Fairus; Mutiara, Mutiara (Universitas Pattimura, 2025)
Writing scientific papers is one of the important activities to demonstrate the professionalism of a teacher. SMKN 5 Langsa has approximately 37 teachers, 20 of whom are civil servants (ASN). The results of interviews with the Deputy Head of School at SMKN 5 Langsa indicate that many teachers are still not skilled in academic writing. Furthermore, they also face difficulties in preparing proper and accurate bibliographies. One of the software that can be used to compile bibliographies is Mendeley. The training is conducted through several stages, include observing the problems faced by the partners. It is followed by the socialization and training on academic writing and the use of Mendeley software. After conducting observations, the team held Focus Group Discussions (FGD) with the community partners. The team provided socialization to the partners regarding the development of teacher competencies in writing scientific articles and the use of Mendeley for academic references. Then, they provided training and mentoring. The conclusion of this activity is that the program ran smoothly, and the partners gained knowledge and PKM training to improve the quality of their scientific writing